Faktor Pemilihan Moda yang Mempengaruhi Keputusan Penggunaan Transportasi Umum (Studi Kasus: Transportasi Umum Trayek Blok M-Pondok Labu) - Guswara, Auliya Ramadhani; Hardi, Ode Sofyan; Munandar, Aris (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
This research is useful for identifying the factors of choosing a mode of transportation, which can influence decision making to use public transportation, on the Blok M-Pondok Labu route. This study uses a quantitative method, with the research subject being the people using the Blok M-Pondok Labu transportation. The sampling technique used random sampling. The data analysis technique used descriptive analysis, and the Spearman rank correlation test. The correlation test uses the calculation of the significance score of alpha (α) 0.005 and the critical table score is 0.195. The mode selection factor is stated to have a significant correlation, if the alpha significance score is <0.005, and the correlation coefficient score is >0.195. This study examines 4 factors of mode selection, namely transportation user factors, travel factors, mode facility factors, and city/zone factors. The results show that the factors of users of transportation modes, travel, and transportation mode facilities have a significant influence on decision making on the use of Blok M-Pondok Labu public transportation. Meanwhile, city/zonal factors do not have a significant influence on the decision making of Blok M-Pondok Labu public transportation.